Digital image watermarking, analysis of current methods - Mohammed, Ghassan N.; Yasin, Azman; Zeki, Akram M. (2012)
The rapid evolution in data transmission by the wide use of the internet, as provided an urgent need to prevent penetration and maintain the confidentiality of this data through the applying of some techniques to hide data within the carrier for example, text, image, audio and Video. A variety of image watermarking techniques have been published in the last few years which attempts to develop techniques and methods which are used to obtain better results through the fact that the changes that took place after the concealment is visible to the human eye. Digital image watermarking is one of the general information hiding problem. This study is to highlight some of these studies and analysis for use in future research and development to get to the best results.